Can managers time the market? Evidence using repurchase price data - Dittmar, Amy; Field, Laura Casares (Journal of Financial Economics, 2015)
Little is known about the price firms pay for stock repurchases. Using a data set of all U.S. repurchases from 2004 to 2011, we compare the actual average price paid monthly in a repurchase with the average market price for the same stock over various horizons. We find that firms repurchase stock at a significantly lower price than the average market price in all sample years. Less frequent repurchasers, firms that repurchase when insiders buy on their own account, and firms that experience low stock returns prior to the repurchase obtain significantly lower prices. After controlling for risk factors, repurchasing firms earn positive returns. Infrequent repurchasers earn a significantly higher return up to three years following the actual repurchase.